Complaints Recording System with Responsive Web at STMIK Atma Luhur - Yohanes Setiawan Japriadi; Sujono Sujono; Anisah Anisah (SISFOTENIKA, 2020)
The IT Departement of STMIK Atma Luhur's (BSI) currently serves complaints related to IT on campus by using Whatsapp group. This is less effective and efficient because it makes the process of complaints recording from a department in a certain time becomes difficult. Website-based complaints recording system with responsive design will be built to solve these problems. The display of responsive web can change according to device that accesses it, so that the user experience when accesses it with mobile device will be same as the one who accesses it with desktop. System development model, method, and tools used in this research are prototyping model, object-oriented method, and Unified Modeling Language (UML), respectively. The built system can be used by employees, lecturers, or students to register accounts, fill complaints, and view it responses by BSI. In addition, BSI can manage data related to complaints, validate accounts, respond to complaints, and print complaints reports with built system. Based on the results of questionnaire recapitulation that has been done, it can be concluded that the built system can accelerate and facilitate the process of complaints submission, response, and management at STMIK Atma Luhur. In addition, the system page display is automatically adjusted to user's device, so the system remains easy and pleasant to use even if accessed with smartphone.